My touch - Turner , Jeffrey; Turner , Jeffrey (Chicago, Illinois Sunbird Books, 2021)
What feels squishy, fluffy, sticky, or soft to you? Talking about sensory experiences can help children process them. In this brightly illustrated board book, an adorable--and relatable--prickly porcupine names and describes a variety of textures, inspiring children and caregivers to talk about how things feel
Linguistic Notions
Keywords: Picture books; Touch Fiction